Prevalence and factors of discordance attitudes toward advance care planning between older patients and their family members in the primary medical and healthcare institution - Ye, Ling; Jin, Genhong; Chen, Min; Xie, Xingyuan; Shen, Shanshan; Qiao, Song (Frontiers in Public Health, 2023)
Background This study aimed at investigating the prevalence and factors of the discordant attitudes toward advance care planning (ACP) among older patients and their family members toward patients' engagement in ACP in the primary medical and healthcare institution. Methods In a cross-sectional study, a total of 117 older patients and 117 family members from Jinhua Fifth Hospital in China were enrolled. The questionnaire included sociodemographic characteristics, functional capacity assessment, and attitudes toward patients' engagement in ACP. Functional capacity assessment scales included the Modified Barthel Index (MBI), the Short-Form Mini-Nutritional Assessment (MNA-SF), the 15-item Geriatric Depression Scale (GDS-15), the Mini-Mental State Examination (MMSE), the Clinical Frailty Scale (CFS), and the SARC-F questionnaire. Results The discordance attitudes toward patients' engagement in ACP between patients and family members accounted for 41(35.0%). In the multivariate logistic analysis, factors associated with higher odds of discordance attitudes toward patients' engagement in ACP included greater age differences between patients and family members (OR = 1.043, 95% CI: 1.007–1.081), lower educational level for family members (OR = 3.373, 95% CI: 1.239–9.181), the patient's higher GDS-15 score (OR = 1.437, 95% CI: 1.185–1.742), and patient's higher MNA-SF score (OR = 1.754, 95% CI: 1.316–2.338). Conclusion Older patients and their family members had little ACP knowledge, and factors that influence discordance attitudes toward patients' engagement in ACP included the age gaps between patients and family members, family members' educational level, patients' depressive symptoms, and patients' nutritional status.